Strategi Manajemen Konflik atas Pendirian Taman Pendidikan Qur’an - Gunarsih, Asma'I; Choiriyah, Siti (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on conflict management tactics in the establishment of non-formal Islamic educational institutions, particularly Taman Pendidikan Al-Qur’an (TPQ), despite the fact that conflicts arising during their development have significant implications for the sustainability and social legitimacy of religious education at the community level. The aim of this study is to identify the types of conflict that occur in the process of founding TPQs, analyze conflict management tactics based on Rahim and Bonoma’s Dual Concern Model, and explore the role of Islamic ethical values in community mediation and reconciliation. Employing a qualitative phenomenological approach, data were collected from eight key informants—including TPQ administrators, religious leaders, community members, and village officials—selected through purposive sampling. Data collection techniques included in-depth interviews, participant observation, and reflective documentation, which were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that all five conflict management strategies—integrating, obliging, compromising, dominating, and avoiding—were effectively internalized through Islamic values such as musyawarah (deliberation), islah (reconciliation), and ukhuwah (brotherhood). This process successfully transformed conflict into an opportunity for moral education and strengthened community social cohesion. The study expands Western conflict management frameworks into a transformational-spiritual model rooted in Qur’anic ethics, offering both theoretical contributions to conflict studies and practical guidance for managing Islamic educational institutions in an ethical, participatory, and values-based manner.